Longitudinal Voice Outcomes Following Serial Potassium Titanyl Phosphate Laser Procedures for Recurrent Respiratory Papillomatosis. (April 2021) - Hung, Wei-Chen; Lo, Wu-Chia; Fang, Kai-Min; Cheng, Po-Wen; Wang, Chi-Te
Objective: Repeated surgical interventions are usually required to control recurrent respiratory papillomatosis (RRP), but at considerable risk of worsened postoperative voice quality. Potassium titanyl phosphate (KTP) laser has been reported to effectively manage RRP; however, voice quality after repeated procedures has not been investigated. Methods: This study recruited 16 patients with RRP treated using KTP laser between 2013 and 2019. KTP laser procedures were performed under general anesthesia via direct suspension laryngoscope or under local anesthesia via flexible endoscope, depending on the need for pathological proof, patient tolerance, and lesion size and location. Disease control was investigated by videolaryngostroboscopy. Voice outcome was evaluated using a 10-item voice handicap index (VHI-10), acoustic and perceptual analyzes. Results: We reviewed the medical records of 11 male and 5 female patients with RRP (age range: 23-73 years). Five patients received KTP laser once, six patients received it 2 to 5 times, and five patients received 6 to 15 procedures. Median VHI-10 decreased from 28.3 to 12.0 points after the initial procedure and were maintained at 10.1 to 11.0 points following subsequent procedures ( P  < .01, generalized estimating equation). Acoustic and perceptual analysis of voice quality also revealed significant improvements ( P  < .01), which remained stable even after 6 to 10 KTP laser procedures. Minor adverse events included slight fibrotic change of vocal folds and glottic web, but these did not significantly alter postoperative voice quality. Conclusion: This longitudinal follow-up study revealed that serial KTP laser procedures can effectively control RRP while preserving phonatory function and maintaining adequate voice quality. Level of Evidence: 4